Associated factors that influenced persistence with basal analog insulin therapy among people with type 2 diabetes: An exploratory analysis from a UK real-world sample. Issue 2 (April 2019) - Idris, Iskandar; Gulati, Kunal; Perez-Nieves, Magaly; Hadjiyianni, Irene; Cao, Dachuang; Tahbaz, Arash; Ivanova, Jasmina; Hassan, Syed Wasi
Highlights: Reasons for insulin continuation were improved physical feeling and glycemic control. Common reasons for interruption or discontinuation were weight gain and hypoglycemia. 56% of participants interrupting because of weight gain actually experienced it. 42.1% of participants interrupting because of hypoglycemia actually experienced it. Important reason for possible re-initiation was persuasion by healthcare provider. Abstract: Aim: Real-world effectiveness of insulin therapy is affected by poor treatment persistence, often occurring soon after initiation. An international cross-sectional survey of people with type 2 diabetes mellitus (T2DM) has been conducted to describe reasons for non-persistence with insulin therapy. Methods: Responders to an online survey in 7 countries were classified as continuers (no gap of ≥7 days), interrupters (interrupted therapy for ≥7 days within first 6 months, then restarted), and discontinuers (terminated therapy for ≥7 days within first 6 months, no restart before survey). We present the results from the United Kingdom (UK) cohort. Results: Of 942 global respondents, 131 were from the UK, having a mean age of 37 years and a mean of 7 years since first T2DM diagnosis. Reasons contributing to insulin continuation (n = 50) were improved physical feeling (52.0%) and improved glycemic control (48.0%). Common reasons for interruption (n = 50) or discontinuation (n = 31), respectively were weight gain (50.0%, 48.4%) and hypoglycemia (38.0%, 25.8%). Most important reason for possible re-initiation for interrupters and discontinuers, respectively was persuasion by physician/healthcare professional (74.0%, 64.5%). Conclusion: The benefits of basal insulin therapy motivated continuers to persist with the treatment; experienced or anticipated side effects contributed to interruption and discontinuation.